Flipping the anatomy classroom: a comparative analysis of 16-week and 8-week courses in a community college - Gopalan, Chaya; Bruno, Elizabeth L.; Daughrity, Sheyenne E.; Nguyen, Kim-Leiloni T. (Frontiers in Education, 2024)
Using flipped teaching modality, a student-centered pedagogical approach, in community college courses remains an understudied area. This study explored the effectiveness of unflipped (UF), partially flipped (PF), and fully flipped (FF) teaching formats within the confines of an accelerated eight-week Introduction to Human Anatomy course at a community college. The purpose of this study was to examine flipped teaching in an accelerated anatomy course by comparing final examination scores between the UF, PF, and FF modalities, compare the effectiveness of flipped teaching between a regular (16-week) and an accelerated anatomy course, evaluate the effect of different teaching modalities on male and female students between a regular and an accelerated course; and examine UF, PF, and FF among the above-median and the below-median students. Students in the FF sections were required to read relevant chapter(s) in the textbook and review slides before class. Students in the PF sections were required to read the textbook and slides for 25% of the chapters. All students took the same final exams and similar section exams. Final exam scores were higher in the regular 16-week course than in the eight-week course for UF (p=0.0219) and PF (p=0.0183) modalities. The 16-week course had significantly higher final examination scores (p=0.0492; n=65) than the eight-week course. Male students scored significantly lower in the eight-week FF course (49.42±13.72) than in the eight-week PF (p=0.006) and 16-week FF (p=0.0008) formats and also compared to female students in the eight-week FF course (p=0.0121). Above-median students in the eight-week course had significantly lower scores in the FF modality (71.35±7.01) compared to PF (80.92±5.30) (p=0.009). Below-median students in the eight-week course had lower scores in the FF modality (52.25±11.48) compared to UF (p=0.0113) and PF (p=0.04). In conclusion, FF in a 16-week anatomy course resulted in higher final exam scores than in the eight-week course. The eight-week FF format affected male student scores. Both above- and below-median groups experienced similar effects when exposed to FF within the accelerated course. Further investigations are essential to inform the refinement of flipped teaching methodologies in community colleges, particularly in the context of accelerated courses.